Edukasi Peluang Usaha Kecil Berdasar Karakteristik Sosial Ekonomi Masyarakat Kecamatan Kutalimbaru - Dewi Mahrani Rangkuty; Suryani Sajar,; Ahmad Yazid; Tarisya Alfadhila (Intitut Agama Islam Nasional Laa Roiba Bogor, 2023)
The purpose of this community service is to increase the understanding of community small business actors in Kutalimbaru sub-district, Deli Sedang Regency about business opportunities based on socio-economic characteristics. The specific target in this community service is that small business actors in the Kutalimbaru sub-district community know what business opportunities are and the concept of socio-economic characteristics how to apply them in the world of household businesses and their impact on household income, for example by becoming a new source of income from small household businesses that have been applied so that they are able to read the problems that occur in the market closest to the settlement, and as well as small markets around the Kutalimbaru sub-district. The materials presented in this community service are: what are business opportunities and socio-economic characteristics, how the impact of business opportunities on household income. Which is related to improving the welfare of households as economic actors in Kutalimbaru sub-district through community knowledge/understanding related to the establishment of small household businesses, target markets and forms of problems that exist in the market. From this community service, the results show that the Kutalimbaru sub-district community already knows and understands business opportunities based on the concept of socio-economic characteristics, so that they start opening small businesses that can increase income that utilizes productivity to become an alternative in increasing income and then can improve welfare through community income. Keywords: Economic; Kutalimbaru; Opportunity; Social; Business